An empirical study of local‐decision‐making‐based software customization in distributed development - Ahmed S. Ghiduk; Abdulrahman M. Qahtani (IET Software)
Abstract Making a decision for the requirements of multi‐stakeholders is a key process, especially in distributed software development projects. Local decision‐making for requirements in distributed software development is really difficult to accomplish as well as communicating these requirements over organizational boundaries and conveying them to the offshore developers is a big task. This study presents an empirical evaluation for the effectiveness of local decision‐making on the customization process of the software in the distributed development against productivity and cost reduction. This empirical evaluation utilizes the Communicating Customization Requirements of Multi‐Clients in a Distributed Domain (CCRD) model. The empirical study estimates the productivity of CCRD in terms of the number of requirements for which decisions are made. In addition, the study estimates the reduction in the total cost of the customization process in terms of the salaries of the required local decision‐makers. Besides, this study finds the critical point at which the CCRD is still valid (i.e. the minimum number of requirements that violate the significance and worthy of CCRD). The study uses a real data set of 18 clients distributed through 16 cities and involved in one customization project requested about 3000 requirements collected in 1290 working hours. The results of this study showed that the local decision‐making improved the productivity of the customization process from 503 requirements in 200 min of simulation to 1,499 requirements. In addition, it reduced 41.5% of the cost. Besides, the results showed that the minimum number of requirements at which CCRD is still valid is 112 requirements.